Removable prosthesis hygiene in elders with Parkinson's disease. (21st November 2017) - Ribeiro, Giselle Rodrigues; Campos, Camila Heitor; Garcia, Renata Cunha Matheus Rodrigues
ABSTRACT: Aim: To evaluate changes in prosthesis hygiene in elders with Parkinson's disease (PD) in response to verbal instruction and positive reinforcement. Methods and Results: Elders with removable prostheses were divided into PD (n = 17) and control (n = 20) groups. Biofilm on prostheses was measured at baseline, and verbal instructions on prosthesis hygiene were given. After 7, 14, and 30 days, biofilm presence was re‐evaluated and the results were shown to participants, with repeated cleaning instruction. At baseline, participants with PD had more biofilm on maxillary prostheses than did controls ( p = 0.009). At 30 days, biofilm presence on maxillary and mandibular prostheses did not differ between groups. Both groups showed reductions in biofilm accumulation on prostheses over time, but this effect took longer to appear on mandibular prostheses in the PD group ( p < 0.05). Conclusion: Verbal instruction and positive reinforcement can improve prosthesis hygiene in elders with and without PD.